Influence of osmotic pressure on the growth of three species of the genus Zoophthora - Jerzy Piątkowski; Ewa Kliczkowska (Acta Mycologica, 2013)
Strains accomodated in the genus Zoophthora are very sensitive to osmotic value of their habitat. Hipertonical molarity of buffers and NaCl decreases the growth, but this effect strongly depends on the species tested and on the kind of buffer. In 0.66% phtalan buffer the growth of Z. lanceolata is completely stopped whereas Z. psyllae and Z. aphrophora is inhibited only in 50% comparing to the control.